WOMEN IN FITNESS: MOTIVATIONS FOR THE PRACTICE OF PHYSICAL ACTIVITIES (Fiep Bulletin - online, 2015)
This study analyzed the representations of bodily aesthetics manifested by women who practice physical activities. An attempt was made to identify the meaning attributed by them to the motivations for the practice of physical activities. The approach applied was qualitative, referenced in the Social Representations Theory. Interviews were made with fifteen women who practice physical activities in a gym in the south zone of the city of Rio de Janeiro. In the list of reasons why the women felt motivated to practice physical activities, health represented the main reason, in opposition to the replies obtained about the reasons why people, in general, feel motivated to physical activities practices. For the latter case, reply number one on the list was aesthetics. Aesthetics ranked as the third personal reason for the practice of physical activities in the former case. This fact allows us to bring up the hypothesis according to which women mention aesthetics in a rather embarrassing way, and their attempt to comply with the demands of the contemporary aesthetical model finds it way to legitimacy through the discourse about health.
Keywords: Bodily Aesthetics; Women; Motivations